Practical safety of using essential medicines and their market products in Thailand - Burapadaja S. (2014)
Safety is one of the very important elements of medicines, especially in daily practice. It is expected that the medicines listed by the Thai Essential Medicine Lists (EML) and their market products registered by the Thai Food and Drug Administration (FDA) should be comparable with respect to practical safety. The objective was to investigate if there are differences in practical safety between anti-infective essential medicines and their products assigned by the two authorities in Thailand. Data were based on Thai EML, Thai FDA registration, and Thailand Index of Medical Specialities 2008. Results showed that Thai EML and Thai FDA divided anti-infective items (n = 101) and their products into groups varying in practical safety. Two thirds of the items and their products were comparable with respect to practical safety, but one third of them were not. The products of the latter were defined as having a lower practical safety compared to their corresponding items. This study has demonstrated that there are differences in practical safety between several essential medicines and their products. Consistent practical safety is very necessary for safe use of anti-infective products. Thus, there should be deliberations between the two authorities to reconsider the practical safety of these items and their products. © 2010 - IOS Press and the authors. All rights reserved.